Dose imaging in a thorax phantom with lung-equivalent volume at the epithermal neutron beam of LVR-15 reactor - Gambarini, G; Vanossi, E; Bartesaghi, G; Carrara, M; Mariani, M; Negri, A; Burian, J; Viererbl, L; Klupak, V; Rejchrt, J (Applied radiation and isotopes, 2009)
A thorax phantom has been designed, consisting of PMMA and PE plates containing a cavity filled with a laboratory-made lung-substitute. Fricke-gel dosimeters have been placed in the lung-substitute volume, and the phantom has been irradiated at the epithermal column of LVR-15 reactor. Absorbed dose images have been obtained for both gamma radiation and charged particles emitted in the (10)B reactions with thermal neutrons. Measurements with thermoluminescence dosimeters (TLDs) and Monte Carlo (MC) calculations have been performed too, in order to attain inter-comparison of results.
Keywords: rychlé neutrony; Gels; Boron Neutron Capture Therapy; Isotopes; nádory plic; Boron; Radiometry; fantomy radiodiagnostické; Radiation-Sensitizing Agents; lidé; Radiotherapy Planning, Computer-Assisted; radiosenzibilizující látky; fotony; Photons; Fast Neutrons; radiometrie; hrudník; Nuclear Reactors; Humans; plánování radioterapie pomocí počítače; Czech Republic; gely; Phantoms, Imaging; izotopy; Thorax; Lung Neoplasms; Česká republika; atomové reaktory; bor; terapie metodou neutronového záchytu (bor-10)